Sequential Extraction, Characterization, and Analysis of Pumpkin Polysaccharides for Their Hypoglycemic Activities and Effects on Gut Microbiota in Mice - Wu, Hui-qing; Ma, Zhi-li; Zhang, De-xin; Wu, Ping; Guo, Yuan-hua; Yang, Fang; Li, De-yuan (Frontiers in Nutrition, 2021)
This study was aimed to extract polysaccharides from pumpkin, characterize the structures of four of them and evaluate their in vitro antioxidant and hypoglycemic activities. Additionally, an animal model of type 2 diabetes mellitus (T2DM) was established and used to determine their hypoglycemic and hypolipidemic effects in vivo, and the underlying mechanisms related to the regulation of gut microbial. Water-extracted crude pumpkin polysaccharides (W-CPP), water extraction and alcohol precipitation crude pumpkin polysaccharides (WA-CPP), deproteinized pumpkin polysaccharides (DPP) and refined pumpkin polysaccharides (RPPs) were sequentially extracted and purified from pumpkin powder by hot water extraction, water extraction and alcohol precipitation, deproteinization and DEAE-52 cellulose gel column, respectively. The extraction and purification methods had significant influence on the extraction yield, physicochemical properties, in vitro antioxidant and hypoglycemic activities. W-CCP and RPPs had the significant positive free radical scavenging capacities and inhibitory activities on α-glucosidase and α-amylase. RPP-3 not only inhibited the uptake of glucose in Caco-2 monolayer, but also promoted excretion of glucose, while RPP-2 had no inhibitory effect. Animal experiment results showed that W-CPP treatment significantly improved the T2DM symptoms in mice, which included lowering fasting blood glucose, reducing insulin resistance, and lowering blood lipid levels. It increased the diversity of intestinal flora and reduced the harmful flora of model mice, which included Clostridium, Thermoanaerobe, Symbiotic bacteria, Deinococcus, Vibrio haematococcus, Proteus gamma, and Corio. At family level, W-CPP (1200 mg/kg) treatment significantly reduced the abundance of Erysipelotrichaceae, and the Akkermanaceae of Verrucobacterium became a biomarker. Pumpkin polysaccharides reshaped the intestinal flora by reducing Erysipelotrichaceae and increasing Akkermansia abundance, thereby improved blood glucose and lipid metabolism in T2DM mice. Our results suggest that W-CCP and RPP-3 possess strong antioxidant and hypoglycemic activities, are potential candidates for food additives or natural medicines.